Internet Addiction and Mental Distress Among Undergraduate Medical Students: A Sequential Explanatory Mixed-Methods Study - Anirban Nandy; Tridibes Bhattacharya; Avijit Dey (International Journal of Health Sciences and Research, 2026)
Background: Problematic internet use is increasingly relevant among medical students because of extensive academic and recreational dependence on digital technology. This study assessed moderate/severe internet addiction, mental distress, associated factors, and experiences underlying severe internet addiction. Methods: A sequential explanatory mixed-methods study was conducted among 200 undergraduate medical students at a teaching hospital in Eastern India. Stratified random sampling selected 50 students from each of four MBBS phases. Internet addiction was assessed using the 20-item Internet Addiction Test (IAT), with scores ≥50 defining moderate/severe addiction. Mental distress was assessed using the SRQ-20, with scores ≥8 indicating distress. Bivariate analyses and separate multivariable logistic regression models were performed. Variables with p